Answer :

Given identity

(a – b)2 = a2 – 2ab + b2


(i) (x – 6)2


Using the given identity


Here a = x, b = 6


= x2 – 2× x × 6 +62


= x2 –12x +36


(ii)(3x – 5y)2


Using the given identity


Here a = 3x, b = 5y


= (3x)2 – 2× 3x × 5y + (5y)2


= 9x2 – 30xy +25y2


(iii)(5a – 4b)2


Using the given identity


Here a = 5a, b = 4b


= (5a)2 –2× 5a × 4b + (4b)2


= 25a2 – 40 ab + 16b2


(iv) (p2 – q2)2


Using the given identity


Here a = p2, b = q2


= (p2)2 – 2 × p2 × q2 + (q2)2


= p4 – 2 p2 q2 + q4


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the product:Karnataka Board - Mathematics Part I

If a, b are ratioKarnataka Board - Mathematics Part I

Use the identity Karnataka Board - Mathematics Part I

Express the folloKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Simplify:

Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Evaluate these usKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I